2017
DOI: 10.1002/elsc.201600178
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of vitamin A palmitate using immobilized lipase produced by recombinant Pichia pastoris

Abstract: In this work, the Candida antarctica lipase B (CALB), produced by recombinant Pichia pastoris, was immobilized and used to synthesize vitamin A palmitate by transesterification of vitamin A acetate and palmitic acid in organic solvent. The reaction conditions including the type of solvent, temperature, rotation speed, particle size, and molar ratio between the two substrates were investigated. It turned out that the macroporous resin HPD826 serving as a carrier showed the highest activity (ca. 9200 U g −1 ) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In the latter method, the formation of covalent bonds can be achieved through amide, ether, thio-ether or carbamate bonds between the support and the enzyme [124][125][126] The immobilization of an enzyme by adsorption is a simple technique with high commercial value due to its simplicity, regular use in large-scale processes, low cost, retention of high enzyme activity, and relatively chemical-free enzyme binding [127]. Supports with different degrees of hydrophobicity were previously used such as butyl Sepabeads and octadecyl Sepabeads [126], decaoctil-Sepabeads [128], macroporous resin HPD826 [129], polypropylene powder [124,130,131] and pore-expanded mesoporous silica (SBA-15) [132]. The use of hydrophobic supports is of particular interest, because these supports mimic the enzymes' natural media and can often promote hyperactivation, highly selective adsorption, purification, increased enantioselectivity, and strong but reversible immobilization, making support reuse possible after the enzyme has been deactivated [133,134].…”
Section: Relevant Immobilization Methods For Recombinant Lipasesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter method, the formation of covalent bonds can be achieved through amide, ether, thio-ether or carbamate bonds between the support and the enzyme [124][125][126] The immobilization of an enzyme by adsorption is a simple technique with high commercial value due to its simplicity, regular use in large-scale processes, low cost, retention of high enzyme activity, and relatively chemical-free enzyme binding [127]. Supports with different degrees of hydrophobicity were previously used such as butyl Sepabeads and octadecyl Sepabeads [126], decaoctil-Sepabeads [128], macroporous resin HPD826 [129], polypropylene powder [124,130,131] and pore-expanded mesoporous silica (SBA-15) [132]. The use of hydrophobic supports is of particular interest, because these supports mimic the enzymes' natural media and can often promote hyperactivation, highly selective adsorption, purification, increased enantioselectivity, and strong but reversible immobilization, making support reuse possible after the enzyme has been deactivated [133,134].…”
Section: Relevant Immobilization Methods For Recombinant Lipasesmentioning
confidence: 99%
“…Recombinant CALB produced by K. phaffii was immobilized and used to synthesize vitamin A palmitate by transesterification of vitamin A acetate and palmitic acid in organic solvent with a conversion ability of 54.3% after 15 cycles [129]. As represented in Figure 5, vitamin A palmitate synthesis could be catalyzed by C. antarctica lipase B.…”
Section: Pharmaceutical Applications Of Recombinant Lipasesmentioning
confidence: 99%
“…Moreover, it was found that the catalytic synthetic activity of TLL@apatite hNFs remained 85.2% of its initial activity after 8 cycles. However, the immobilized lipase CALB after 8 cycles remained only 81.9% (47) and about 63.0% (14) of its initial activity in the same catalytic synthesis of vitamin A palmitate with each cycle of only 6 h.…”
Section: Effect Of Reaction Time On Vitamin a Palmitate Yieldmentioning
confidence: 98%
“…Of course, in biocatalysis, the immobilized enzymes have various advantages in continuous practice (13) and are attracting more attentions than the free one. For example, the immobilized Candida antarctica lipase B (CALB) has been used to catalyze the synthesis of vitamin A palmitate (14).…”
Section: Introductionmentioning
confidence: 99%
“…10.0-15.0 mg/kg of vitamin A was added in Bangladesh Standards (Fiedler et al, 2015). Yao et al (2017) immobilised Candida antarctica lipase B (CALB) and used to synthesise vitamin A palmitate by transesterification of vitamin A acetate and palmitic acid. Previously reported that the synthesis method allowed directly from C15-vinyl-b-ionol to vitamin A acetate, by the Wittig reaction with the C5-aldehyde, b-formylcrotyl acetate 28 (Parker et al, 2016).…”
Section: Introductionmentioning
confidence: 99%